High priority traffic separation in shared Ethernet networks - Ricardo Moraes (2005)
In this paper, it is proposed an enhanced algorithm for the collision resolution in shared Ethernet networks. Such algorithm, referred as high priority Binary Exponential Backoff (h-BEB), provides high priority traffic separation, enabling the support of real-time communications. To our best knowledge, the h-BEB algorithm is the first collision resolution algorithm that allows Ethernet standard devices to coexist with modified stations in the same network segment, imposing higher priority for the transfer of privileged traffic. The probabilistic and simulation analysis of the traffic separation shows that it guarantees for an h-BEB station a predictable and significantly smaller access delay, when compared with the access delay for standard Ethernet stations.